Tipni indeks slovenskih ljudskih pravljic Živalske pravljice in basni - Kropej Telban, Monika (ZRC SAZU, Založba ZRC, 2015)
This book ('Type Index of Slovenian Folktales - Animal Tales and Fables') is the first of the comprehensive body of systematization of Slovenian folktales along the lines of the latest, revised edition of the Types of International Folk Tales by Hans-Jörg Uther (2004). It includes Slovenian animal tales and fables that have been listed among the first 299 numbers of the international classification system. It contains archaic, internationally comparable material which was previously difficult to access and is now published for the first time in a comprehensive and systematic form. With the transfer of the latest scientific results to the Slovenian research sphere~additional studies and comments~and the application of the international classification system for the classification of material it greatly facilitates further development of the discipline while simultaneously including the Slovenian narrative tradition in a broader international context. Since each folktale type includes examples of folktales the book will also attract the attention of the general public.